(untitled) (Anclajes, 2019)
Maca Albornoz and her Roman Circus are secondary characters along three novels about the indigenous upheavals in Peruvian Manuel Scorza’s pentalogy. Female protagonism, blurring of gender definition and concession of principal roles to protagonists identified only by their physical or mental challenges, are unusual themes in Indigenist tradition. Nevertheless, we found them in these novels. Following Paul B. Preciado’s assertion that diversity, sexual as well as functional, are inscribed in the body, in addition it is possible to propose that a rebellious counter-proposal could also emerge from these same bodies. The contribution those personages offer to the reader are essential moments of rebellion that compensate the defeat of the principal attack conducted by the leader Agapito Robles. Our proposal sustains that the described rebellion, that can easily be placed in line with Somato-political’s paradigms because of the description of complexities of gender definition as well as the breaking of traditional roles ascribed to protagonists with functional challenges, are mere strategies, in the same fashion as many others that gave Scorza the title of innovator of the traditional Indigenism. Scorza’s final objective could have been to convince the reader, to emotionally involve him/her (Ubilluz) in the rebellious fury that characterized the indigenous upheavals’ epic in the quest to recover their land.